THE INFLUENCE OF THE WORK ENVIRONMENT AND CAREER DEVELOPMENT ON EMPLOYEE PRODUCTIVITY MEDIATED BY JOB SATISFACTION - Kosasih Kosasih; Ni Desak Made Santi Diwyarthi; Fitri Rezeki (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
Quantitative research with an explanatory research method was used in this study. The research aimed to study the influence of the dependent variable on the independent variable. For this purpose, the study enlisted the participation of one hundred individuals and employed structural analysis methods employing Partial Least Square or PLS software. This research investigates the factors that most influence employee productivity, including work environment, career development opportunities, and job satisfaction, with job satisfaction as the moderating variable. It is possible to conclude, based on the study of the research data and the conversations that took place in the part before this one, that the Work Environment has a positive and significant effect on Employee Productivity in CV Multi Lestari Utama. It has been determined that CV Multi Lestari Utama's Career Development Program has a negligible impact on Employee Productivity. When job satisfaction positively and meaningfully impacts employee productivity, this is exactly what we are talking about. In CV Multi Lestari Utama. Job satisfaction does not have a positive impact, either directly or indirectly, on the workplace environment, which in turn does not help employee productivity. Although employee satisfaction might affect productivity in CV Multi Lestari Utama directly.